Analysis of Measurement of Financial Difficulties and Financial Report Fraud (A Case Study at PT Asabri (Persero) 2010-2018) - Fajar Yulianto Dwi Kusuma; Isna Putri Rahmawati (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
This study aims to examine the financial health condition and whether there is an indication of fraudulent financial statements or not at PT ASABRI (Social Insurance for the Armed Forces of the Republic) in 2010-2018 by using the Altman Z-Score, Springate S-Score, Grover G-Score, Beneish M-Score, and Dechow F-Score methods. PT ASABRI became the object of the study due to the result of an audit conducted by the BPK (The Audit Board of the Republic of Indonesia) in 2021 that found fraud in financial management and investment funds at PT ASABRI. To measure financial distress, the researchers used the Altman, Springate, and Grover models. While to examine financial statement fraud, the researchers used the Beneish and Dechow models. The results revealed that each model showed varied results. In the financial distress model, the Altman Z-Score could show financial distress 4 times while the Springate S-Score showed financial distress 5 times in 9 years of observation. Moreover, the other models showed different results. The Grover G-Score model did not indicate any financial distress at PT ASABRI. While in the fraud model, the Beneish M-Score could detect indications of fraudulent statements at PT ASABRI 5 times in 8 years of observation. Different conditions occurred in the Dechow F-Score model that did not show fraudulent financial statements at PT ASABRI in 9 years of observation, from 2010 to 2018.